A cross-sectional survey examining cardiopulmonary resuscitation training in households with heart disease - Cartledge, S.; Finn, Judith; Smith, K.; Straney, L.; Stub, D.; Bray, Janet (Elsevier BV, 2019)
Background: Heart disease significantly increases the risk of further cardiac events including out-of-hospital cardiac arrest (OHCA). Given the majority of OHCAs occur in the home, family members of those with heart disease should be trained in cardiopulmonary resuscitation (CPR). Aim: To describe CPR training rates in households with heart disease, and examine if training increases knowledge, confidence and willingness to perform CPR in this population. Methods: A cross-sectional, telephone survey was conducted with adults residing in Victoria, Australia. Findings: Of 404 respondents, 78 (19.3%) reported the presence of heart disease in their household. Prevalence of CPR training was the same among households with (67.9%) and without (67.8%) heart disease, with the majority (51.5%) receiving training more than five years ago. There were no significant differences in barriers to training- the most prevalent barrier was lack of awareness to seek training. Among households with heart disease, physical ability was the most common concern relating to the provision of CPR, while households without heart disease described decreased confidence. Those with heart disease in their household who were CPR trained, had higher self-ratings of CPR knowledge and confidence, and were more willing to perform CPR (all p < 0.05). Conclusions: A large proportion of Victorians with heart disease in their household did not have recent CPR training. CPR training should be targeted to high-risk households containing a member with heart disease, as knowledge and confidence in skills are increased. Cardiac health professionals are well placed to provide CPR training information during patient contacts.